Location Strategies of Multinationals from Emerging Countries in the EU Regions - Riccardo Crescenzi; Carlo Pietrobelli; Roberta Rabellotti (London School of Economics and Political Science (LSE), European Institute, 2015)
This paper contributes to the current debate in both Economic Geography and International Business on the nature and strategies of Multinational Enterprises (MNEs) from emerging countries (EMNEs). The paper fills a relevant gap in the existing literature by shedding new light on the location strategies of EMNEs at the national and regional level, looking at their investment drivers and systematically comparing them with those of multinationals from advanced countries (AMNEs). The empirical analysis looks at the location choices of MNEs in the European Union (EU-25) regions and unveils that EMNEs follow distinctive location strategies. Their attraction into large regional markets is similar to AMNEs as well as their irresponsiveness to efficiency seeking motives. Conversely, the most knowledge-intensive investments of EMNEs respond mainly to two 'attraction' factors: strategic assets (in the form of local technological dynamism) and the agglomeration of foreign investments in the same business functions. In addition, both the national and the regional levels are simultaneously relevant to EMNEs decisions.
Keywords: F21; F23; O33; R12; R58; 330; multinationals; emerging countries; regions; European Union